Valoración de la inserción de la inteligencia artificial en el ámbito jurídico: un análisis frente al proceso del ente acusador en etapa de indagación (2021)
This article addresses the relationship that may exist between artificial intelligence (AI) and the accusatory criminal system, specifically as an assistant for the Prosecutor’s Office, claiming that, through the facts and the probative material collected by the judicial police, the latter is analyzed by a software, which can determine the criminal conduct through the information obtained. This through a qualitative research with the application of a theoretical deductive method, consisting of the review of databases, bibliography and statistics, beginning with the presentation of the function of the prosecutor’s office in the investigation phase. It continues with a statistical analysis, legal informatics and the location of artificial intelligence among its branches, a study of comparative law with Mexico, Argentina, United States, Canada, and Australia, to respond to the legal problem identified in the face of the inadequate classification of punishable conducts, which in turn violates the different procedural guarantees. The above, by generating recommendations for the implementation of a software that manages and analyzes the factual and legal circumstances to determine more easily the conduct.